RETRACTED: Justification for selecting the neural network type for inclusion in the architecture of the developed medical information system - Berezovsky Vladimir; Vygovskaya Natallia (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001